Image of an Atrocity: Ivan (Hovhannes) Aivazovsky’s Massacre of the Armenians in Trebizond 1895 - Vazken Khatchig Davidian (Études Arméniennes Contemporaines, 2018)
The essay introduces the celebrated nineteenth-century Russian Armenian seascape painter Ivan (Hovhannes) Aivazovsky’s (1817-1900) Massacre of the Armenians in Trebizond in 1895 as one of the most important of the artist’s multifarious responses to the systematic series of massacres unleashed upon the Ottoman Armenian population during 1894-1897. An important document of intellectual engagement with a recorded event of wholesale massacre, the work is presented as an early manifestation of atrocity imagery within an Armenian historical context, radically introducing the representation of violence into an already established Russian Armenian visual taxonomy of Ottoman Armenian victimhood. It is a work that survives only through its mediated reproduction in Russian Armenian lawyer and editor Grigor Djanshiev’s illustrated Russian language Fraternal Help for the Suffering of the Armenians in Turkey, a tome produced to raise funds for the survivors of the mass violence and publicise the events to a wider audience. The essay examines the claim as implied in the work’s caption of the image as truthful depiction of an actual well-documented event, the 8 October 1895 massacre in the eponymous city, and asks whether it represents, rather, an imagined dramatization subordinating human drama to the artist’s customary concern for a Romantic aesthetic. The essay further considers the propagandistic attributes of the work, manifested via its mass circulation and wide dissemination, particularly as incorporated into Fraternal Help.